Health Information Management for Medical Records, Medical Coding, Health Administration, and Medical Secretaries - Alrasheedi, Mohammad Saad Saud; Adel Darwish Almahwari; Alaa Abdulaziz Almuhanna; Rifah Muhammed Saad Aldosseri; Sharoog Abdulrhman Alkuraiea; Marwah Hamoud Albanaqi; Mohammed Obeid Misfer Aldosari; Fares Abdulaziz Sharid Al-Mutairi; Mishari Fuhaid Mohammed Al-Mutairi; Aeshah Bawkaryah Yhazaylaee; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Health Information Technology (HIT) has become a foundational component of modern healthcare systems, integrating hardware, software, and standardized data processes to support clinical, administrative, and research functions. It plays a critical role for health information management professionals, including medical records specialists, medical coders, health administrators, and medical secretaries, whose responsibilities depend on accurate, secure, and accessible health data. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to examine the role of HIT in supporting healthcare accountability, improving patient and population health outcomes, enhancing healthcare delivery efficiency, and reducing overall healthcare costs, with particular emphasis on its impact on health information management professionals. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative-based analytical approach was used, synthesizing evidence from established literature, policy discussions, and real-world case examples. The article reviews key HIT components such as electronic health records (EHRs), computerized physician order entry (CPOE), health information exchanges (HIEs), and interoperability standards, and evaluates their influence on clinical decision-making, operational workflows, and population health monitoring. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> HIT was shown to improve patient safety through error reduction, support population health surveillance, streamline administrative workflows, and enable data-driven decision-making. However, challenges including high implementation costs, interoperability limitations, data security risks, and user-related inefficiencies persist. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> HIT remains essential for effective healthcare delivery, provided its challenges are addressed through strategic investment, training, and system optimization.